Digital Literacy-Based Reciprocal Teaching Learning Model on Indonesian Learning Outcomes - Wahyullah Alannasir (Lembaga Sembilan Tiga Community, 2023)
One way to improve the quality of education through information technology is to implement digital culture in schools. The study was conducted to see the effect of the digital knowledge-based reciprocal teaching model on Indonesian learning outcomes. This research is a quasi-experimental research with a nonequivalent control group design. The population is grade VI students of SD Negeri Parang Tambung 1 Makassar City with a sample of 36 students based on Isaac and Michael's table. Observation, documentation and tests as data collection techniques. The data analysis technique uses a t test with the condition that it meets the normality and homogeneity tests. The results showed a significant influence of reciprocal teaching learning models based on digital literacy on Indonesian learning outcomes. This can be seen from the hypothesis test obtained 0.021 so that the value of sig. (2tailed) < 0.05. The implementation of the learning process using a reciprocal teaching model based on digital literacy in grade VI students of SD Negeri Parang Tambung 1 Makassar City is said to be good. This is seen from the activeness and independence of students during the learning process, increasing student learning outcomes and seen from the implementation of aspects observed on the obervasi sheet in learning.